Climate change will require more agile business continuity planning. (July 2015) - Kingswood, Matt
Abstract : Climate change will bring new challenges to IT managers and business continuity and disaster recovery (BC/DR) planners in years to come. Experts – including researchers from the Met Office and Newcastle University, and Edward Hanna, professor of climate change at the University of Sheffield – suggest climate change could lead to an increase in severe weather phenomena such as flash flooding and 'weather bombs', intense storms with low centre pressure triggered by jet stream changes. 1–3 This severe weather can in turn lead to blackouts. Severe weather events can lead to power outages, floods and other disasters that can severely disrupt your business. And climate change may increase outbreaks of disease, which could leave you short-staffed. Responses to these threats need to be flexible and deep. Using the right resources and enlisting the assistance of strategic vendors can alleviate some of the stress during an unexpected interruption and help you improve your ability to get back to business quickly when disaster strikes, explains Matt Kingswood of IT Specialists.